Pengaruh Bahan dan Lama Waktu Perendaman Benih terhadap Pematahan Dormansi Benih Cabai Rawit (Capsicum frutescens) - Ari Istanti; Laelatul Rizqiyah; Astri Iga Siska; Aldy Bahaduri Indraloka; Abdul Holik (Jurnal Riset Rumpun Ilmu Tanaman, 2025)
More than 20% of the seeds sown did not germinate normally. The problem of low chili pepper seedling growth rates was caused by low germination rates. Internal factors contributing to low germination rates in chili pepper seeds had yet to be solved. This research aimed to analyze the effect of materials and duration of seed soaking of cayenne pepper (Capsicum frutescens) as well as the results of the soaking treatment for cayenne pepper seeds (Capsicum frutescens). This research used factorial Completely Randomized Design (CRD). The first factor, namely soaking material (P), includes control treatment or no  soaking treatment (K), warm water with a temperature of 50˚C (P1), KNO3 solution with a concentration of 1% (P2), and colchicine solution with a concentration of 0.1 % (P3). The second factor, namely duration of seed soaking (T), includes soaking time of 12 hours (T1) and soaking time of 24 hours (T2). There were 7 treatments with each treatment having 3 replications. This research carried out dormancy observations for 7 days. The data analysis for this research was in the form of quantitative data using Two Way ANOVA and DMRT further. The parameters observed included germination capacity, and germination rate. The results of this researc that 0.1% colchicine solution (P3) and 24 hour soaking time (T2) was the best materials and seed soaking for cayenne pepper seeds with 95% germination capacity.